Assessment of myocardial oxygenation, strain, and diastology in MYBPC3-related hypertrophic cardiomyopathy: a cardiovascular magnetic resonance and echocardiography study. (21st January 2019) - Grover, Suchi; Lloyd, Rachael; Perry, Rebecca; Lou, Pey Wen; Haan, Eric; Yeates, Laura; Woodman, Richard; Atherton, John J; Semsarian, Chris; Selvanayagam, Joseph B
Abstract: Aims: Myocardial oxygenation is impaired in hypertrophic cardiomyopathy (HCM) patients with left ventricular hypertrophy (LVH), and possibly also in HCM gene carriers without LVH. Whether these oxygenation changes are also associated with abnormalities in diastolic function or left ventricular (LV) strain are unknown. Methods and results: We evaluated 60 subjects: 20 MYBPC3 gene positive patients with LVH (G+LVH+), 18 MYBPC3 gene positive without LVH (G+LVH−), 11 gene negative siblings (G−), and 11 normal controls (NC). All subjects underwent 2D transthoracic echocardiography and cardiovascular magnetic resonance imaging for assessment of ventricular volumes, mass, and myocardial oxygenation at rest and adenosine stress using the blood oxygen level dependent (BOLD) technique. Maximal septal thickness was 20 mm in the G+LVH+ group, vs. 9 mm for the G+LVH− group. As expected, the G+LVH+ group had a more blunted myocardial oxygenation response to stress when compared with the G+LVH− group (−5% ± 3% vs. 2% ± 4%, P < 0.05), G− siblings (−5% ± 3% vs. 11% ± 4%, P < 0.0001) and NC (−5% ± 3% vs. 15% ± 4%, P < 0.0001). A blunted BOLD response to stress was also seen in G+LVH− subjects when compared with gene negative siblings (2% ± 4% vs. 11% ± 4%, P < 0.05) and NC (15% ± 4%, P < 0.050). G+LVH+ patients exhibited abnormal diastolic function including lower Eʹ, higher E to E ʹ ratio and greater left atrial area compared with the G+LVH− subjects who all had normal values for these indices. Conclusion: Myocardial deoxygenation during stress is observed in MYBPC3 HCM patients, even in the presence of normal LV diastolic function, LV global longitudinal strain, and LV wall thickness.